Dynamics of the photoacoustic response of single-element PZT transducers to pulse burst excitation - Cherkashin, Maxim N.; Brenner, Carsten; Putro, Widodo Dwi; Döpke, Benjamin; Gerhardt, Nils Christopher; Hofmann, Martin R. (Photons Plus Ultrasound: Imaging and Sensing 2017)

Depth-filtering in common-path digital holographic microscopy - Finkeldey, Markus; Göring, Lena; Brenner, Carsten; Hofmann, Martin; Gerhardt, Nils Christopher (Optics express)

Backside imaging of a microcontroller with common-path digital holography - Finkeldey, Markus; Schellenberg, Falk; Gerhardt, Nils Christopher; Hofmann, Martin; Göring, Lena (Practical holography XXXI: Materials and Applications)

Investigations on polarization oscillation amplitudes in spin-VCSELs - Lindemann, Markus; Gerhardt, Nils Christopher; Hofmann, Martin R.; Pusch, Tobias; Michalzik, Rainer (Vertical-Cavity Surface-Emitting Lasers XXI)

Common-path holographic objective for conventional photographic camera - Besaga, Vira; Gerhardt, Nils Christopher; Hofmann, Martin R.; Maksimyak, Peter P. (Novel Optical Systems Design and Optimization XX)

High-frequency polarization dynamics in spin-lasers - pushing the limits - Lindemann, Markus; Hofmann, Martin R.; Gerhardt, Nils Christopher; Pusch, Tobias; Michalzik, Rainer (Spintronics X)

Thermally induced birefringence tuning of 37 GHz in VCSELs - Lindemann, Markus; Gerhardt, Nils Christopher; Hofmann, Martin R.; Pusch, Tobias; La Tona, Eros; Michalzik, Rainer (2017 Conference on Lasers and Electro-Optics Europe & European Quantum Electronics Conference (CLEO/Europe-EQEC 2017))

Digital holographic microscopy of buried specimen using a common-path reflective setup - Finkeldey, Markus; Brenner, Carsten; Gerhardt, Nils Christopher; Hofmann, Martin R.; Göring, Lena (DGaO-Proceedings)

Frequency tuning of polarization oscillations: Toward high-speed spin-lasers - Lindemann, Markus; Pusch, Tobias; Michalzik, Rainer; Gerhardt, Nils Christopher; Hofmann, Martin R. (Applied Physics Letters)
Spin-controlled vertical-cavity surface-emitting lasers (spin-VCSELs) offer a high potential to overcome several limitations of conventional purely charged-based laser devices. Presumably, the highest potential of spin-VCSELs lies in their ultrafast spin and polarization dynamics, which can be significantly faster than the intensity dynamics in conventional devices. Here, we experimentally demonstrate polarization oscillations in spin-VCSELs with frequencies up to 44 GHz. The results show that the oscillation frequency mainly depends on the cavity birefringence, which can be tuned by applying mechanical strain to the VCSEL structure. A tuning range of about 34 GHz is demonstrated. By measuring the polarization oscillation frequency and the birefringence governed mode splitting as a function of the applied strain simultaneously, we are able to investigate the correlation between birefringence and polarization oscillations in detail. The experimental findings are compared to numerical calculations based on the spin-flip model.

Large laser spots and fault sensitivity analysis - Schellenberg, Falk; Finkeldey, Markus; Gerhardt, Nils Christopher; Hofmann, Martin R.; Moradi, Amir; Paar, Christof

Local binary patterns for differentiation of brain tissue types inoptical coherence tomography images - Lenz, Marcel; Krug, Robin; Gerhardt, Nils Christopher; Schmieder, Kirsten; Hofmann, Martin; Dillmann, Christopher; Welp, Hubert (Biomedical engineering)

Large laser spots and fault sensitivity analysis - Schellenberg, Falk; Finkeldey, Markus; Gerhardt, Nils Christopher; Hofmann, Martin R.; Moradi, Amir; Paar, Christof (2016 IEEE International Symposium on Hardware Oriented Security and Trust (HOST 2016))

Common-path depth-filtered digital holography for high resolution imaging of buried semiconductor structures - Finkeldey, Markus; Schellenberg, Falk; Gerhardt, Nils Christopher; Paar, Christof; Hofmann, Martin (Practical Holography XXX: Materials and Applications)

Influence of birefringence splitting on ultrafast polarization oscillations in VCSELs - Lindemann, Markus; Gerhardt, Nils Christopher; Hofmann, Martin R.; Pusch, Tobias; Michalzik, Rainer (Vertical-cavity surface-emitting lasers XX)

Microscopic description of a spin laser - Gerhardt, Nils Christopher; Faria, Paulo E., Jr.; Xu, Gaofeng; Lee, Jeongsu; Sipahi, Guilherme M.; Žutić, Igor (APS March Meeting 2016)

Frequency tuning of polarization oscillations in spin-polarized vertical-cavity surface-emitting lasers - Lindemann, Markus; Hofmann, Martin R.; Gerhardt, Nils Christopher; Pusch, Tobias; Michalzik, Rainer (Semiconductor Lasers and Laser Dynamics VII)

Birefringent vertical cavity surface-emitting lasers - toward high-speed spin-lasers - Lindemann, Markus; Gerhardt, Nils Christopher; Hofmann, Martin R.; Pusch, Tobias; Michalzik, Rainer (Semiconductor Lasers and Laser Dynamics VII)

Dynamics of double-pulse photoacoustic excitation - Brenner, Carsten; Göring, Lena; Döpke, Benjamin; Cherkashin, Maxim N.; Gerhardt, Nils Christopher; Hofmann, Martin R. (Photons Plus Ultrasound: Imaging and Sensing 2016)

Common-path digital holography microscopy of buried semiconductor specimen - Göring, Lena; Finkeldey, Markus; Gerhardt, Nils Christopher; Hofmann, Martin R. (Adaptive Optics: Analysis, Methods & Systems)

Birefringence tuning of VCSELs - Lindemann, Markus; Gerhardt, Nils Christopher; Hofmann, Martin R.; Bou Sanayeh, Marwan; Michalzik, Rainer; Pusch, Tobias (Semiconductor Lasers and Laser Dynamics VII)